Micrornas e seu papel na variação da expressão gênica e de fenótipos de interesse em bovinos da raça nelore - Dias, Marina Cerqueira (Universidade Federal de São Carlos, 2025)
Nellore cattle are highly relevant to the Brazilian beef market because they are well adapted to the tropical climate. Artificial selection is a useful technique in the pursuit of improved herd productivity and sustainability, with animals exhibiting advantageous phenotypes being chosen as parents for future generations. Phenotypic expression in cattle is a complex process affected by gene expression. Thus, molecules such as microRNAs (miRNAs), which play a regulatory role in gene expression, are relevant targets for studying the manifestation of observable traits. This study tested the correlation between the expression profile of liver, muscle, and rumen mRNAs from a population of 52 Nelore cattle and the phenotypes of rib eye area (REA), subcutaneous fat thickness (SFT) between the 11th and 12th ribs, residual feed intake (RFI), and residual methane emission (RME). The total RNA content of the tissue samples was extracted, analyzed, and sequenced to obtain miRNA and mRNA sequences. The raw data were processed and analyzed, which involved quality control, mapping, alignment, identification, batch correction, and filtering steps. The resulting miRNAs and mRNAs, along with the phenotypic data of each animal, were used for correlation tests between the miRNAs/mRNAs expressed in each tissue and the REA, SFT, RFI and RME phenotypes using the PCIT algorithm. The results of this tissue-specific analysis were organized into correlation networks. Afterwards, target-seeking and functional enrichment analyses were performed to identify the target genes of miRNAs significantly correlated with one of the phenotypes in at least one tissue and to find the biological pathways in which these target genes participate. The results of the study revealed candidate genes for further investigation, such as CYP2R1, DNAJC28, WWOX, LYRM1, GRAMD1B, MPC1, and TIPARP. These genes had already been associated in previous studies with traits related to carcass and meat quality or feed efficiency in cattle. Furthermore, the biological pathways regulating the actin cytoskeleton and mTOR signaling, enriched for candidate genes, also proved to be interesting targets for a better understanding of the direct and indirect regulatory role of miRNAs.
Micrornas and their role in the variation of gene expression and phenotypes of interest in nellore cattle
Keywords: Correlação; Bos indicus; Fenótipos; Pecuária; Bioinformática; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL; 2. Fome Zero e Agricultura Sustentável